Numerical Simulation of Metal Hydride Battery Heat Conducting Matrix Heat-stressed and Deformed State - Avramenko, A.N.; Levterov, A.M.; Gladkova, N.Yu. (Проблеми машинобудування, 2018)
When using numerical methods, the heat-stressed state of the heat-conducting matrix of a cylindrical metal hydride battery is considered. З використанням чисельних методів розглядається теплонапружений стан теплопровідної матриці металогідридного акумулятора циліндричної форми. С использованием численных методов рассматривается теплонапряженное состояние теплопроводящей матрицы металлогидридного аккумулятора цилиндрической формы.